Asthma and Allergic Disease Prevalence in a Diverse Sample of Toronto School Children: Results from the Toronto Child Health Evaluation Questionnaire (T-CHEQ) Study - Sharon D Dell; Richard G Foty; Nicolas L Gilbert; Michael Jerrett; Teresa To; Stephen D Walter; David M Stieb (Canadian Respiratory Journal)
BACKGROUND: Asthma is the most common chronic disease in children.